Occupational stress and alternatives of intervention: a bibliometric study (Research, Society and Development, 2020)
In various professions it is necessary for the worker to spend several hours of his day in the workplace. Depending on the demands, pressures and levels of knowledge and skills, the professional will be subject to occupational stress. Occupational stress management is a very relevant theme, as it can affect the employee's physical and psychological health, reducing their quality of life and productivity. In this paper, we verified that there was an increase in the number of published works on occupational stress from 1990 to 2018. For this, a bibliometric study was performed on the platforms ScienceDirect and Google Scholar. The results showed that given the relevance, the number of papers published on the three platforms consulted has grown in general over time. An analysis of the content of the works most closely related to this research proposal revealed that meditation and relaxation are the most popular interventions; however, cognitive behavioral interventions have the greatest positive effects. With the research, it was also possible to indicate the gaps that still remain open in the literature.